Crystal structure and mesogenic behaviour of a new fluorene derivative: 9, 9‐dimethyl‐2, 7‐bis(4‐pentylphenyl)‐9H‐fluorene. Issue 11 (4th October 2019) - Gupta, Sakuntala; Choudhury, Tanmay; Dmochowska, Ewelina; Kula, Przemyslaw; Borbone, Fabio; Centore, Roberto
Abstract : A new mesogenic compound containing the fluorene moiety exhibits enantiotropic nematic liquid crystalline behaviour with melting at 125 °C and isotropization at 175 °C. The crystallographically independent unit contains two molecules oriented face‐to‐edge with respect to each other. Abstract : The title compound, C37 H42, is a new mesogenic compound containing the fluorene moiety. It exhibits enantiotropic nematic liquid crystalline behaviour with melting at 125 °C and isotropization at 175 °C. The crystallographically independent unit contains two molecules oriented face‐to‐edge with respect to each other. The two molecules have nearly the same conformation of the bis‐phenyl fluorene moiety. The molecular packing in the crystal phase is nematic‐like.